Forensic biology - Houck, Max M. (Boston : Elsevier/AP, Academic Press is an imprint of Elsevier, 2015)
Provides coordinated expert content from world-renowned leading authorities in forensic biology. Covering the range of forensic biology, this volume in the Advanced Forensic Science Series provides up-to-date scientific learning on DNA analysis. Technical information, written with the degreed professional in mind, brings established methods together with newer approaches to build a comprehensive knowledge-base for the student and practitioner alike. --
Section 1 Introduction -- Principles of forensic science -- Forensic classification of evidence -- Section 2 Methods -- Capillary electrophoresis : basic principles -- Section 3 Analysis -- DNA extraction and quantification -- Short tandem repeats -- Section 4 Interpretation -- DNA-statistical probability -- Statistical interpretation of evidence : Bayasian analysis -- Parentage : testing and kinship analysis -- Section 5 Professional issues -- Crime scene to court -- Section 6 Additional topics.
Statement of responsibility from cover.
Includes bibliographical references and index.
Keywords: Forensic biology; Forensic sciences